Water emulsion of the essential oil of Nepeta rtanjensis Diklić & Milojević: potential use as a bioherbicide - Prijović, Mladen P.; Nikolić, Bogdan R.; Dragićević, Ivana Č.; Nestorović Živković, Jasminan M.; Dmitrović, Slavica S; Giba, Zlatko S.; Jovanović, Vladan D. (Archives of Biological Sciences, 2024)
Paper description: Essential oils can be used in allelopathic relationships between plants. The effects of a water emulsion of Nepeta rtanjensis Diklić & Milojević essential oil (NrEO) on seed germination and seedling growth of 5 weed species was examined. Stellaria media (L.) Vill. was the most sensitive, 0.1% NrEO completely inhibited the germination of Amaranthus retroflexus and Artemisia vulgaris L., and reduced germination of Ambrosia artemisiifolia L. to 50%; Cephalaria transsylvanica (L.) Schrad. ex Roem. & Schult was the most tolerant. The water emulsion of the essential oil of rtanjensis could be developed to control invasive and allergenic weeds. Abstract: Plant protection with natural products is a new trend in environmentally friendly agriculture. Nepeta rtanjensis Diklić & Milojević is an endemic and critically endangered plant species in Serbia. We explored the phytotoxic potential of a water emulsion of Nepeta rtanjensis essential oil (NrEO) with high amounts of trans,cis-nepetalactone on five weeds. The most sensitive was Stellaria media (L.) Vill., as NrEO (from 0.013% to 0.1%) completely inhibited germination. Germination of Amaranthus retroflexus L. and Artemisia vulgaris L. was completely inhibited at the highest applied concentrations of NrEO (0.1%), while Ambrosia artemisiifolia L. germination was reduced to 48% at the same concentration of NrEO. The most tolerant species was Cephalaria transsylvanica (L.) Schrad. ex Roem. & Schult. as the final germination rate at the highest applied concentration of NrEO (0.1%) was 81%, like the control (82%). To our knowledge, this is the first time the interaction of essential oils on the germination and growth of A. vulgaris and C. transsylvanica is reported. The germination dynamics of S. media in pots with soil were significantly inhibited when the soil was initially treated with the highest applied concentration of the NrEO water emulsion (1%). Spraying S. media seedlings with NrEO significantly inhibited growth parameters (shoot height, shoot fresh weight, and the number of nodes) at the higher applied concentrations of NrEO (0.5% and 1%). Therefore, the water emulsion of the essential oil of N. rtanjensis could be potentially developed for use in the control of invasive and allergenic weeds.